1996
DOI: 10.1111/j.1432-1033.1996.0365h.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Factor VIII Light‐Chain Cleavage by Thrombin and Factor Xa

Abstract: Activation and limited proteolysis of factor VIII have been investigated with respect to the role of the heavy-chain region Lys713-Arg740. The kinetics of factor VIII activation have been analyzed in a system consisting of human factor VIII, factor IXa, factor X, phospholipids, and thrombin or factor Xa. Plasma-derived factor VIII is activated by thrombin with a second-order rate constant of 3.3 t O.3X1O6 M-' s-l, which proved to be slightly higher than for activation by factor Xa. The second-order rate consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…Specific activity values for R1689H and R1689Q as measured using onestage clotting and enzyme-linked immunosorbent assays were 47 Ϯ 3 and 9.3 Ϯ 2% that of wild-type factor VIII, respectively. These values suggested a near-normal phenotype for the R1689H variant, whereas the R1689Q mutation approximated a mild-hemophilic phenotype, which is consistent with previous results (17,18) showing that cleavage at Arg-1689 makes modest contributions to the specific activity of factor VIII.…”
Section: Characterization Of Recombinant Factor VIII Protein-supporting
confidence: 80%
See 1 more Smart Citation
“…Specific activity values for R1689H and R1689Q as measured using onestage clotting and enzyme-linked immunosorbent assays were 47 Ϯ 3 and 9.3 Ϯ 2% that of wild-type factor VIII, respectively. These values suggested a near-normal phenotype for the R1689H variant, whereas the R1689Q mutation approximated a mild-hemophilic phenotype, which is consistent with previous results (17,18) showing that cleavage at Arg-1689 makes modest contributions to the specific activity of factor VIII.…”
Section: Characterization Of Recombinant Factor VIII Protein-supporting
confidence: 80%
“…Cleavage at Arg-372 is a critical step in thrombin activation of factor VIII as it exposes a cryptic functional factor IXa-interactive site in the A2 domain (15), whereas cleavage at Arg-1689 liberates factor VIII from von Willebrand factor (16) and contributes to factor VIIIa specific activity (17,18). Although cleavage at Arg-740 represents a fast step relative to cleavages at other P1 residues in the activation of factor VIII (19), the influence of Arg-1689 cleavage on cleavages in the heavy chain remains unknown.…”
mentioning
confidence: 99%
“…Cleavage at Arg 1689 in Factor VIII Proteins by ThrombinPrevious results have suggested that the presence of heavy chain promotes thrombin proteolysis of light chain (14). The above observations monitored using the anti-A2 domain antibody support this contention.…”
Section: Characterization Of Recombinantsupporting
confidence: 73%
“…Cleavage at Arg 372 exposes a cryptic functional factor IXainteractive site in the A2 domain (11), while cleavage at Arg 1689 liberates factor VIII from von Willebrand factor (12) and contributes to factor VIIIa specific activity (13,14), thus making both sites essential for procofactor activation. Although it is known that cleavage at Arg 740 represents a fast step relative to cleavage at other sites in the activation of factor VIII (15), the role for this event is unknown.…”
mentioning
confidence: 99%
“…A monoclonal antibody directed against this region inhibited thrombin activation of factor VIII (51,52), and recombinant B-domainless factor VIII molecules in which this region was partially deleted were observed to require higher thrombin concentrations for efficient activation of the procofactor (52,53). Furthermore, in experiments using a factor VIII chimera where A2 residues 712-736 were replaced with a high affinity thrombin site from the serpin, heparin cofactor II showed increased rates of both cleavages at Arg 372 by thrombin and overall factor VIII activation (54), suggesting that the C-terminal region of A2 influences cleavages at distal sites in the factor VIII molecule.…”
Section: Discussionmentioning
confidence: 99%